Stability Analysis of 3D UAV Gimbal using Flexible Body - Ruseno, Neno (BRIN Publishing, 2023)
Unmanned aerial vehicle (UAV) application in visual object tracking requires a gimbal to stabilize the camera in following the object’s movement. External disturbance and gimbal stability are the issues in this application. This study aims to analyze disturbance effects and study the stress and modal analysis on UAV gimbal using flexible body concepts. The three-dimensional (3D) gimbal is modeled using the RecurDyn software consisting of 3 arms and a camera. Each of the arms is connected using a revolute joint and a rotational force to represent a motor. The considered disturbances are step, pulse, ramp, and sine wave input. The PID controller is used to stabilize the gimbal arm from the gravity of the camera and external disturbance. The result shows that the PID controller is robust to step, pulse, and ramp disturbance, but not to the sin wave disturbance. In addition, the second arm of the gimbal is the most stressed component and is prone to vibration.